Integrating environmental sustainability into set-up efficiency: Eco-efficient Quick Changeover - Braglia, Marcello; Afy-Shararah, Mohamed; Di Paco, Francesco; Marrazzini, Leonardo; Salonitis, Konstantinos (Springer, 2025)
In an era of increasing environmental and competitive pressures, manufacturing firms are continually challenged to improve production efficiency while minimizing ecological impacts. This paper introduces a novel Lean methodology named Eco-efficient Quick Changeover (EQC). It emerges as a strategic response to these dual imperatives, integrating the rapid set-up principles of Lean manufacturing with comprehensive sustainability considerations. EQC employs a systematic four-phase approach that begins with assembling a multidisciplinary team, followed by quantifying both time and environmental losses through an innovative Losses Matrix, examining the interdependencies of these losses via a Cause and Effect Matrix, and ultimately prioritizing corrective actions through the Ranking Matrix with a novel Green Set-up Index. A case study conducted in a plastic water bottle production facility revealed that this integrated strategy can reduce changeover time by 72%, lower energy consumption by 62%, and achieve substantial reductions in water usage, CO₂-equivalent emissions, and waste generation. These results underscore the potential of EQC to deliver significant operational improvements while advancing environmental performance, thereby offering a holistic framework that aligns with current sustainable development objectives.
Keywords: 46 Information and Computing Sciences; 40 Engineering; 49 Mathematical Sciences; 12 Responsible Consumption and Production; Industrial Engineering & Automation; Set-up; SMED; Lean manufacturing; Green manufacturing; Environmental sustainability; Operational efficiency